Utility of multi‐channel surface electromyography in assessment of focal hand dystonia. Issue 3 (17th July 2013) - Sivadasan, Ajith; Sanjay, M.; Alexander, Mathew; Devasahayam, Suresh R.; Srinivasa, Babu K.
ABSTRACT Introduction Surface electromyography (SEMG) allows objective assessment and guides selection of appropriate treatment in focal hand dystonia (FHD). Methods Sixteen‐channel SEMG obtained during different phases of a writing task was used to study timing, activation patterns, and spread of muscle contractions in FHD compared with normal controls. Customized software was developed to acquire and analyze EMG signals. Results SEMG of FHD subjects (20) showed "early onset" during motor imagery, rapid proximal muscle recruitment, agonist‐antagonist co‐contraction involving proximal muscle groups, "delayed offset" after stopping writing, higher rectified mean amplitudes, and mirror activity in contralateral limb compared with controls (16). Muscle activation latencies were heterogenous in FHD. Conclusions Anticipation, delayed relaxation, and mirror EMG activation were noted in FHD. A clear pattern of muscle activation cannot be ascertained. Multi‐channel SEMG can aid in objective assessment of temporal‐spatial distribution of activity and can refine targeted therapies like chemodenervation and biofeedback. Muscle Nerve48: 415–422, 2013